2020
DOI: 10.35473/jhhs.v2i2.49
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Beban dengan Kemampuan Keluarga Merawat Activity Of Daily Living (ADL) Pasien Skizofrenia

Abstract: Family burden that felt by family can decrease the family’s ability to take care of patient’s ADL. The aim of this study is to analyze the correlation between family burden and family’s ability to take care of Activity Of Daily Living (ADL) of schizophrenia patients. The design descriptive correlation with cross sectional approach. The population of this research was the whole of the patient’s family with the amount of samples were 94 respondents with purposive sampling. The data collection used questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research, consistent but not precisely the same, demonstrated that implementing caregiver interventions including six sessions of psychoeducation over 2-3 months, employing brainstorming, case sketches, role-playing, and video clips, significantly reduced caregiver emotional expression (Shetty, Math, Marimuthu, & Rawat, 2023). Caregiver psychoeducation applied materials Auditory hallucinations in schizophrenia: Psychoeducation among caregivers to help patients develop effective coping strategies Daryanto 1 *, Mohammad Syukri 1 , Sri Martini 2 , Sri Endriyani 2 , Mila Triana Sari 3 1 Departemen Keperawatan Politeknik Kesehatan Departemen Kesehatan, Jambi 2 Departemen Keperawatan Politeknik Kesehatan Departemen Kesehatan, Palembang 3 Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi Corresponding author: *E-mail: daryanto2766@gmail.com related to schizophrenia, whereas in this study, the focus of the materials in the modules and videos was more specific, targeting auditory hallucination care (Addiba & Choiriyyah, 2020). Psychoeducation for caregivers using auditory hallucination care module media and videos impacted the burden of schizophrenia patient caregivers both before and after treatment in both the intervention and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research, consistent but not precisely the same, demonstrated that implementing caregiver interventions including six sessions of psychoeducation over 2-3 months, employing brainstorming, case sketches, role-playing, and video clips, significantly reduced caregiver emotional expression (Shetty, Math, Marimuthu, & Rawat, 2023). Caregiver psychoeducation applied materials Auditory hallucinations in schizophrenia: Psychoeducation among caregivers to help patients develop effective coping strategies Daryanto 1 *, Mohammad Syukri 1 , Sri Martini 2 , Sri Endriyani 2 , Mila Triana Sari 3 1 Departemen Keperawatan Politeknik Kesehatan Departemen Kesehatan, Jambi 2 Departemen Keperawatan Politeknik Kesehatan Departemen Kesehatan, Palembang 3 Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi Corresponding author: *E-mail: daryanto2766@gmail.com related to schizophrenia, whereas in this study, the focus of the materials in the modules and videos was more specific, targeting auditory hallucination care (Addiba & Choiriyyah, 2020). Psychoeducation for caregivers using auditory hallucination care module media and videos impacted the burden of schizophrenia patient caregivers both before and after treatment in both the intervention and control groups.…”
Section: Discussionmentioning
confidence: 99%